(untitled) (Medico Legal Update, 2020)
Background: In today’s society, adolescents have seen an increase in violence. Teenagers face many situations that cause these problems. There are several factors: the mass media, peer pressure and society’s view of the “ideal” person. Television, radio and newspapers are all ways to get messages to people. One might watch a violent movie and decide to reactivate the scenes, causing harm to themselves or others. The hidden meanings of racism and hatred are put into music. Teenagers hear the words of their supposed role models and think it’s good to follow in their footsteps. Objectives: Assessment of violence among Late Adolescence. Methodology: A descriptive cross-sectional study was carried out in order to achieve the stated objectives. The study has begun from 1st September 2018. Settings of the Study: The settings of the study include (41) High secondary schools which are distributed in (3) Districts of Al-Najaf Governorate, urban (23) schools and rural (18) schools, these schools are systematic randomly selected. Result: Showed that the most majority is low violence 51.2%. Conclusions: The majority of the sub-domain of violence was the trend towards violence and Most of the study sample had low violence. Recommendations: Supporting educational method by the Educational Committee that limits violent behavior of adolescents in schools, such as (moving away from scenes of an aggressive nature, beating, violence, fighting, quarrels and blood scenes) and the teacher devotes part of the lesson time to clarifying issues and harms of violence and to show the benefits of tolerance and contentment. And The school administration cooperated with the teenager’s family to identify the causes of his violence. Finally, The Ministry of Education is working to create posters that reject violence and suspend it throughout the school.